THE VALIDITY AND REALIBILITY OF IELTS SPEAKING RUBRIC FOR INLINGUA INTERNATIONAL TEACHERS - Purwanti Taman (Universitas Pamulang, 2019)
AbstractThe field of English for specific purposes (ESP) has developed rapidly to become a major force in English language teaching. IELTS (International English Language Testing System), as one of the ESP branch, is one of the biggest ESL tests needed world-wide.This study was conducted to find validity and reliability of IELTS speaking rubric between three teachers who assess speaking ability for the same students in the same class. This would enable IELTS teachers to measure the students’ speaking ability likely in the same band area. The participants of this quantitative study were 21 Indonesian graduate students who were taking English for Pre-departure program of their Master’s Degree abroad, an English for Academic Purpose (EAP) class. The result shows that the teachers in Inlingua Internatinal English training produce reliable and valid results of the speaking IELTS subtest; even though they have different working span experience because they use the same rubric. Also, the correlation between one group of scores to others are significant and linear. This can be reference for the future in the way Inlingua International maintain their teachers’ marking scheme.Keywords: IELTS, validity, realibility, speaking rubric, ESP